The evidence is in: Repetitive transcranial magnetic stimulation is an effective, safe and well-tolerated treatment for patients with major depressive disorder. (July 2022) - Fitzgerald, Paul B; George, Mark S; Pridmore, Saxby
Despite more than 25 years of research establishing the antidepressant efficacy of repetitive transcranial magnetic stimulation, there remains uncertainty about the depth and breadth of this evidence base, resulting in confusion as to where repetitive transcranial magnetic stimulation fits in the therapeutic armamentarium in the management of patients with mood disorders. The purpose of this article is to provide a concise description of the evidence base supporting the use of repetitive transcranial magnetic stimulation in the context of the stages of research that typically accompanies the development of evidence for a new therapy. The antidepressant efficacy for the use of repetitive transcranial magnetic stimulation in the treatment of depression has been established through a relatively traditional pathway beginning with small case series, progressing to single-site clinical trials and then to larger multisite randomised double-blind controlled trials. Antidepressant effects have been confirmed in numerous meta-analyses followed more recently by large network meta-analysis and umbrella reviews, with evidence that repetitive transcranial magnetic stimulation may have greater efficacy than alternatives for patients with treatment-resistant depression. Finally, repetitive transcranial magnetic stimulation has been shown to produce meaningful response and remission rates in real-world samples of greater than 5000 patients. The evidence for the antidepressant efficacy of repetitive transcranial magnetic stimulation therapy is overwhelming, and it should be considered a routine part of clinical care wherever available.